Skryjelites auritus gen. et sp. nov. and Quasimolites quasimodo gen. et sp. nov.--two new middle Cambrian hyolithids (?Mollusca) from the Czech Republic - Valent, Martin; Fatka, Oldřich; Szabad, Michal; Micka, Václav; Marek, Ladislav (Zootaxa, 2015)
Two new endemic genera and species of extinct group of Hyolitha, Skryjelites auritus gen. et sp. nov. and Quasimolites quasimodo gen. et sp. nov. are described and illustrated from the Buchava Formation of the Barrandian area (Czech Republic).
Keywords: Mollusca; Body Size; Animal Structures; Animal Distribution; velikost orgánu; měkkýši; Animals; Organ Size; Česká republika; rozšíření zvířat; velikost těla; zvířata; anatomické struktury zvířat; Czech Republic